INTEGRATING ARTIFICIAL INTELLIGENCE IN SECONDARY ENGLISH INSTRUCTION: REGULATORY PRACTICES AND ISSUES ENCOUNTERED - Catherine D. Aguilar; Mary Angeline A. Bautista; Karyl Gibrette M. Duque; Lean Lauren C. Flores; Archie Kierra R. Gaddi; Ma. Cristal Jade S. Malibiran; Angelica Mae M. Taqueban; Joyce Mariz A. Tulio; Shemuel S. Serrano; Ryan R. Pecson (INJOSEDU: International Journal of Social and Education, 2025)
Artificial Intelligence (AI) became popular in the 21st century. With its features that mostly mimicked what humans can do or beyond humans' limits, its prevalence in multiple professional fields was simply noticeable and was also widely used in education. However, data on how teachers integrated these AI tools into their instruction was still insufficient. With that, the study collected further data on how high school English teachers incorporated AI tools in their English instruction. It also proposed a compendium of the regulatory practices on integrating AI tools in English instruction and addressing the issues encountered. The phenomenological research design, a qualitative research method, was used in this study. Ten English teachers participated in the study, which was held in a public integrated and a national high school in the Province of Bataan, Philippines. Purposive sampling was the method used to choose them. The researchers examined participant replies using Colaizzi's (1978) Descriptive Phenomenological Analysis (DPA). Results indicate that AI tools like chatbots enhance engagement and personalization but may affect critical thinking. AI boosts student engagement through gamification and personalized learning, optimizes tasks, and provides immediate feedback. However, challenges like tech access and proficiency underscore the need for professional development. The study offers a practical guide for integrating AI, addressing technology access and over-reliance, and providing interactive tools and personalized learning strategies, emphasizing ethical guidelines and professional training to improve teaching outcomes and student engagement. The proposed guide helps educators navigate AI in English language teaching.